Ustawa o swobodzie działalności gospodarczej a najistotniejsze zmiany w ogólnym prawie podatkowym - Urban, Alicja (The Free Enterprise Act and the Biggest Changes of Fiscal Law in Poland, 2005)
The new act on free enterprise replaced the act on enterprise, which was binding since 2001. The new law lays down the rules by which one creates a favourable environment for investing in Poland and provides for the correct usage of fiscal law. The changes assure the competitiveness of Poland in the European Union. The act of 2nd July on free enterprise binds polish administration to help businesses or companies and: • to use for their procedures the shortest period (4 or 8 weeks to the tax control), • to restrict the official authorities interference into enterprises activities. In addition, the new law protects businesses or companies from responsibility, in case they are provided with a written guidance from the official authorities. The favourable changes in the new law are the provisions making it easier to start up a business. The upper threshold for cash transfer in business operations has been raised. The new act amends to the fiscal law, limits the number of audits and introduces an annual maximal audit timeframe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 76-90